Evaluasi Kesesuaian Penyimpanan Obat di Instalasi Gudang Farmasi Puskesmas Rambah Pasir Pengaraian Kabupaten Rokan Hulu - Isna Wardaniati; Ermida Diani Hasibuan; Adrian Mulya (LPPM Universitas Abdurrab, 2024)
Errors in drug storage at the health center can cause the drug to be damaged, resulting in a decrease in the level/potency of the drug so that when consumed by patients it becomes ineffective in therapy. This study aims to evaluate the suitability of the drug storage process in the pharmaceutical warehouse installation of the Rambah Pasir Pengaraian Health Center against the pharmaceutical service standards at the health center. This research is an observational study with a descriptive cross-sectional design with the object of research on pharmaceutical preparations and infrastructure facilities at the Rambah Pasir Pengarian Health Center Warehouse Installation. The results of the study showed that the suitability of facilities was 94.17%, drug storage was 90.9%, drug storage layout was 100% and the level of suitability of recording drug stock cards was 100%. It is concluded that drug storage at the pharmaceutical warehouse installation of the Rambah Pasir Pengaraian Health Center, Rokan Hulu Regency is in accordance with the Regulation of the Minister of Health of the Republic of Indonesia of 2019 concerning Pharmaceutical Service Standards at Puskesmas.